Effects of E-Cigarette Exposure on Prenatal Life and Childhood Respiratory Health: A Review of Current Evidence - Mescolo, Federica; Ferrante, Giuliana; La Grutta, Stefania (Frontiers in Pediatrics, 2021)
In the last decade, widespread use of E-cigarettes (EC) has occurred all over the world. Whereas a large amount of evidence on harm to children from conventional cigarette exposure is available, data on health effects in this population throughout different vulnerability windows are still a matter of concern. Exposure to EC during pregnancy may compromise placental function, resulting in fetal structural abnormalities. Specifically, this may cause physio-pathologic changes in the developing lung, which in turn may impair respiratory health later in life. Furthermore, evidence suggests that the use of EC can cause both short- and long-term respiratory morbidity in the pediatric population and there is great concern for a future generation of youth with nicotine dependence. The low parental perception of the risks connected to EC exposure for children increases their susceptibility to harmful effects from passive vaping. This minireview aims to summarize the current evidence focusing on: i) prenatal effects of EC passive exposure; ii) post-natal respiratory effects of EC exposure in youth; iii) parental attitudes towards EC use and perception of children’s health risks connected to EC exposure.